Forecasting Australia's Olympic performance: Australia to suffer post host letdown in Athens - Clarke, S. R. (2004)
At the Sydney Olympics, 6.3% of the medals handed out were won by Australia - 16 Gold, 25 silver and 17 Bronze medals. But Australians should be warned not to expect a repeat performance in Athens. This paper looks at how nations generally perform in the Olympics after that in which they have acted as host nation. Australia`s last games figures were inflated by the home ground advantage, and analysis shows countries invariably perform worse in their `post host` Olympics. By analysing how countries perform following their host Olympics, we can estimate the proportion of medals Australia will win in Athens. We also analyse Australia`s past medal tallies at all Olympics to predict their Athens tally by an alternative method. However Australia has a history of winning a lower than expected proportion of gold medals, and we should expect no more than 25% of the medals won will be gold. I estimate Australia will win 4.2% of available medals. Aided by the ever increasing number of medals awarded, this will be about 40 medals, made up of 10 gold 14 silver and 16 bronze.